Understanding the Importance of Location, Time, and People in Mobile Local Search Behavior - Teevan, Jaime; Karlson, Amy; Amini, Shahriyar; Brush, A.J.; Krumm, John (Mobile HCI 2011, 2011)
People often search for local information (e.g., a restaurant, store, gas station, or attraction) from their mobile device. We show, via a survey of 929 mobile searchers at a large software company, that local searches tend to be highly contextual, influenced by geographic features, temporal aspects, and the searcher’s social context. While location was reported to be very important, respondents looked for information about places close to their current location only 40% of the time. Instead, they were often in transit (68% of our searchers) and wanted information related to their destination (27% of searchers), en route to their destination (12%), or near their destination (12%). Additionally, 63% of our participants’ mobile local searches took place within a social context and were discussed with someone else. We discuss these findings to present a picture of how location, time, and social context impact mobile local searches.